2022
DOI: 10.1108/irjms-09-2021-0129
|View full text |Cite
|
Sign up to set email alerts
|

A study on the effect of team support and emotional exhaustion on organizational citizenship behavior of nurses in COVID-19 pandemic: mediation by team commitments

Abstract: PurposeNurses need to display organizational citizenship behavior (OCB) for taking care of patients; uninterrupted care to coronavirus disease 2019 (COVID-19) patients in a stressful situation may result in emotional exhaustion and it hinders nurses' exercise of OCB. One perceives support when positive exchanges with team leaders and members (LMX) and team and members (TMX) take place for the benefit of self and the unit and lead to a feeling of commitment to the work team; the exchange facilitates the dischar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…When the organisation seems to support their employees and when the values of collaboration and participation are emphasised, this can result in higher displays of OCB as supported by other studies carried out by Dasgupta (2021) and Alshaabani et al (2021). The Department saw a heightened display of OCB during COVID-19, in terms of the loyalty employees extended to their organisation and their colleagues -which illustrates how Citizenship Behaviours are discretionary and do not form part of any job-related performance requirements (Benuyenah, 2021).…”
Section: Organisational Structure and Organisational Citizenship Beha...mentioning
confidence: 64%
See 1 more Smart Citation
“…When the organisation seems to support their employees and when the values of collaboration and participation are emphasised, this can result in higher displays of OCB as supported by other studies carried out by Dasgupta (2021) and Alshaabani et al (2021). The Department saw a heightened display of OCB during COVID-19, in terms of the loyalty employees extended to their organisation and their colleagues -which illustrates how Citizenship Behaviours are discretionary and do not form part of any job-related performance requirements (Benuyenah, 2021).…”
Section: Organisational Structure and Organisational Citizenship Beha...mentioning
confidence: 64%
“…Results reported that respondents agreed that teamwork and collaboration were critical to an organisation during a crisis like the COVID-19 pandemic. Moreover, Dasgupta (2021) asserted that OCB can arise as a personal choice; however, during the pandemic, healthcare workers like nurses exhibited OCB because they needed to perform duties that are not within their job scope or description, as they voluntarily performed other duties while the healthcare system was overburdened (Buhaid & Buheji, 2022).…”
Section: Organisational Structure and Organisational Citizenship Beha...mentioning
confidence: 99%
“…The results of this study identify COVID-19-related stressors that cause emotional exhaustion will inhibit OCB behavior. (Dasgupta, 2022).…”
Section: Perception Of the Company's Work Safety Implementationmentioning
confidence: 99%
“…Nurses are the frontline healthcare professionals who toiled a lot to take care of huge traffic of indoor and outdoor patients during the pandemic times. The third paper by Dasgupta (2022) examined how organizational citizenship behaviour (OCB) of such nurses is influenced by team support and emotional exhaustion. Further, the mediating role of team commitment has been explored between OCB and other constructs like team support and the emotional exhaustion relationship.…”
mentioning
confidence: 99%